Everything must change, so that the world can remain the same: In memory of the life and work of Elmar Altvater - Birgit Mahnkopf (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Elmar Altvater was a renowned political economist and professor at the Otto-Suhr-Institute of Freie Universität Berlin from 1970 until 2006. Until his death in 2018 he was a point of reference for several generations of students, left-wing academics and politicians, trade union activists, representatives of civil society organizations in Germany, across Europe and in Latin America. He became one of the few academics in Germany who based the analysis of contemporary economic and political developments on a critical reading of Marxian approaches to understand the historical cycles of growth, recession and crisis in modern capitalism. The following text attempts to sketch some elements of a remarkable leftist intellectual history of the Federal Republic of Germany through the prism of Elmar Altvater while referring to some of the political initiatives Elmar Altvater was involved in and touching on some of the most important topics he has dealt with: the causes and consequences of the numerous debt crisis; the role of neoliberalism which emerged in the course of crisis of world finance since the late 1970s; the impact of "finanzialization" on social cohesion and politics at national, European and international level and, most importantly, his attempt to analyze the degradation of nature as the "price of progress" - on the basis of an ecologically expanded critique of political economy.
Keywords: 330; Marx; capitalism; critical political economy; debt crisis; globalization; nature